Evolution of energy and nutrient intake in Brazil between 2008-2009 and 2017-2018 - Verly Junior, Eliseu; Marchioni, Dirce Maria; Araujo, Marina Campos; Carli, Eduardo De; Oliveira, Dayan Carvalho Ramos Salles de; Yokoo, Edna Massae; Sichieri, Rosely; Pereira, Rosangela Alves (Revista de saúde pública, 2021)
To assess the evolution of energy and nutrient intake and the prevalence of inadequate micronutrients intakes according to sociodemographic characteristics and Brazilian regions. The food consumption of 32,749 individuals from the National Dietary Survey of the Household Budget Survey 2008-2009 was analyzed by two food registries, as well as 44,744 subjects from two 24-hour recalls in 2017-2018. Usual intake and percentage of individuals with consumption below the average recommendation for calcium, magnesium, phosphorus, copper and zinc, vitamins A, C, D, E, thiamine, riboflavin, pyridoxine and cobalamin were estimated. Sodium intake was compared to the reference value to reduce the risk of chronic diseases. Analyses were stratified by sex, age group, region and income. Mean daily energy intake was 1,753 kcal in 2008-2009 and 1,748 kcal in 2017-2018. The highest prevalence of inadequacy (> 50%) in the two periods were calcium; magnesium; vitamins A, D and E; pyridoxine and, only among adolescents, phosphorus. There was an increase in the prevalence of inadequate vitamin A, riboflavin, cobalamin, magnesium, and zinc among women, and riboflavin among men. The prevalence of inadequacy decreased for thiamine. Sodium intake was excessive in approximately 50% of the population in both periods. The highest variations (about 50%) in the prevalence of inadequacy between the lowest and highest income (< 0.5 minimum wage and > 2 minimum wages per capita) were observed for vitamin B12 and C in both periods. The North and Northeast regions had the highest prevalence of inadequacy. Both surveys found high prevalence of inadequate nutrient intake and excessive sodium intake. The inadequacy varies according to income strata, increasing in the poorest regions of the country.